Evoke emotion through typography / Muhammad Hadi Anuar - Anuar, Muhammad Hadi (Faculty of Art and Design, 2020)
Typography, the design, or selection, of letter forms to be organized into words and sentences to be disposed of in blocks of type as printing upon a page, Typography and the typographer who practices it may also be concerned with other, related matters, the selection of paper, the choice of ink, the method of printing, the design of the binding if the product at hand is a book, but the word typography without modifier most usually denotes the activities and concerns of those most involved in and concerned with the determination of the appearance of the printed page (Warren E. Preece, 2019).A typeface is a collection of letters. While each letter is unique, certain shapes are shared across letters. A typeface represents shared patterns across a collection of letters. Typefaces that are selected for their style, legibility, and readability are most effective when following the fundamental principles of typographic design. A design for a set of characters. A font is the combination of typeface and other qualities, such assize, pitch, and spacing.